National identity and the varieties of capitalism.The Danish experience - Campbell, John L.; Hall, John A.; Pedersen, Ove K. (Montreal, 2006)
In 14 comparative essays the book analyzes the success of Denmark's national political economy. Contributors to 'National Identity and the Varieties of Capitalism' draw from the literature on capitalism and small states and corporatism to explore why this is the case. They find that Danish political and economic institutions facilitate bargaining and consensus building in ways that have enabled the state, businesses, and labour unions to adapt to the challenges of globalization.